Domestic violence events involving autism: a text mining study of police records in New South Wales, 2005-2016. (October 2020) - Hwang, Ye In; Zheng, Lidan; Karystianis, George; Gibbs, Vicki; Sharp, Kym; Butler, Tony
Highlights: Text mining was applied to domestic violence police records in Australia. Domestic violence involving autism most commonly involves parent-child relationships. Autistic domestic violence more commonly involves intellectual disability. Abstract: Background: Recent research and high-profile media cases have suggested an association between autism spectrum disorder and violent behaviour. Whilst certain characteristics of autism may make individuals vulnerable to increased involvement with the police, either as a victim or person of interest, evidence regarding this is scant. The present study used a population-based dataset to describe the characteristics of domestic violence events involving autistic and non-autistic adults. Methods: Text mining and descriptive statistics were applied to police-recorded data for 1, 601 domestic violence events involving autism and 414, 840 events not involving autism in the state of New South Wales, Australia from January 2005 to December 2016. Results: The relationship between autistic victims and perpetrators was predominantly familial or carer whereas events not involving autism were predominantly involved intimate partners. Abuse types and injuries sustained were similar for both autistic and non-autistic events. The most common mental conditions present in autistic perpetrators were developmental conditions and intellectual disability, whilst non-autistic perpetrators most commonly reported psychoactive substance use or schizophrenia. Conclusions: These results highlight the need to further understand the risk factors for strain and violence in relationships between autistic adults and their family members or carers, especially for those with comorbid behavioural developmental conditions. Given the uniqueness of domestic violence involving autism found in this study and the potentially unique nature of the circumstances surrounding these events, appropriate police awareness and training in relation to autism is needed.